Frequency and Associations of Adverse Reactions of COVID-19 Vaccines Reported to Pharmacovigilance Systems in the European Union and the United States - Montano, Diego (Frontiers in Public Health, 2022)
Introduction. This study aims to provide a risk assessment of the adverse reactions related to the COVID-19 vaccines manufactured by AstraZeneca, Janssen, Moderna and Pfizer-BioNTech which have been in use in the European Union and the United States between December 2020 and October 2021. Methods. Data from the European Database of Suspected Adverse Drug Reaction (EudraVigilance) and the Vaccine Adverse Events Reporting System (VAERS) from 1990 to October 2021 are analysed. More than 11 million adverse reactions of about 2 million persons are included. The population-level vaccine exposures to COVID-19 and non-COVID-19 vaccines comprised more than 400 million and 2.7 billion, respectively. The adverse reactions are classified with the Common Toxicity Criteria (CTC) categories. COVID-19 vaccine exposures and adverse reactions reported between December 2020 and October 2021 are compared to non-COVID exposures and adverse reactions reported between 1990 to 2020. Absolute and relative risk estimates are calculated by CTC categories and COVID-19 vaccines for the EU and US populations aged 18 years and older. Results. A higher risk of reporting serious adverse reactions was observed for the COVID-19 vaccines in comparison to the non-COVID-19 vaccines. Individuals age 65 and older were associated with a higher frequency of death, hospitalisations and life-threatening reactions than younger individuals (relative risk estimates between 1.59 99% CI [1.50-1.69] to 11.82 99% CI [11.26-12.41]). Outcome onset of serious adverse reactions occurred within the first seven days after vaccination in about 77.6% to 89.1% of cases. The largest absolute risks were observed for allergic, constitutional reactions, dermatological, gastrointestinal, neurological reactions and localised and non-localised pain. The largest relative risks between COVID-19 vs. non-COVID-19 vaccines were observed for allergic reactions, arrhythmia, general cardiovascular events, coagulation, haemorrhages, ocular, sexual organs reactions and thrombosis. Conclusion. The present study provides an overview of adverse reactions frequently reported to the pharmacovigilance systems following COVID-19 vaccination in the EU and US populations. Despite the limitations of passive reporting systems, these results may inform further clinical research investigating in more detail the pathophysiological mechanisms potentially associated with the COVID-19 vaccines.